Phase Transition Behaviors of Lead-Free (Na1/2Bi1/2)TiO3-BaTiO3 Single Crystals Studied by Inelastic Light Scattering Spectroscopy. Issue 1 (2nd January 2016) - Lee, Byoung Wan; Ko, Jae-Hyeon; Li, Xiaobing; Luo, Haosu
Abstract : Acoustic anomalies of (1- x )(Na1/2 Bi1/2 )TiO3 - x BaTiO3 (NBT- x BT) with x = 0.05 were investigated over a wide temperature range of from 900°C to −200°C by using Brillouin light scattering. The sound velocity of the longitudinal acoustic mode propagating along the [100] direction showed a substantial softening, while the acoustic attenuation coefficient of this mode exhibited a large increase in the paraelectric phase. These anomalies were attributed to the formation and growth of noncentrosymmetric polar regions in the paraelectric phase, which was supported by the appearance of the strong polarized central peak. The absence of any sharp or discontinuous changes in the acoustic properties seems to suggest that the polar regions remain short-ranged and do not form macroscopic polar domains at low temperatures, which may be attributed to the inherent A-site disorder induced by random substitutions of Bi, Na and Ba cations.